Anesthesia Management in Patients with Moyamoya Disease with Superficial Temporal ArteryMiddle Cerebral Artery Bypass: Case Report - Virayanti, Luh Putu Diah; Suarjaya, I Putu Pramana; Ryalino, Christopher; Surya Panji, Putu Agus; Senapathi, Tjokorda Gde Agung (Jurnal Neuroanestesi Indonesia, 2025)
Moyamoya Disease (MMD) is a rare unknown disease that causes occlusion of the blood vessels of the brain in adults and children. There are several methods of operation that can be used for therapy, such as direct bypass and indirect bypass. Direct bypass is a method to connect the branches of the external carotid artery, usually the superficial temporal artery (STA), to the branching of the internal carotid artery, generally the Middle Cerebral Artery. Its potentially created several problems such as secondary brain injury and changes in hemodynamic. We use general anesthesia based on neuroanesthesia concepts to protect brain perfusion and maintain the patient's hemodynamic stability. In this patient, induction was carried out using remifentanil TCI Minto mode 4-6 ng/ml, Propofol TCI Schneider target effect 46 mcg/ml and Rocuronium 40 mg IV. We also add SCALP Block with Bupivacaine 0.25% volume of 23 ml. Before induction, an arterial line was installed on the right radial artery to determine hemodynamic changes, to protect cerebral perfusion pressure. The patient was stable during the operation and extubated immediately after the surgery. The patient returned to his initial state of consciousness and was admitted to the ICU for 48 hours.